Self-control and curiosity: has curiosity been an overlooked concept in the crime/deviance decision-making process? - Arneklev, Bruce J. (Deviant behavior, 2023)
We conducted an empirical test of Gottfredson and Hirschi’s, 1990 A General Theory of Crime in this exploratory study to introduce the concept of curiosity to criminological theory. Specifically, we tested whether self-control was significantly associated with curiosity and whether curiosity significantly predicted a crime/deviance index beyond the effects of self-control. An original eight item curiosity scale was created that measured both an attitudinal curiosity dimension and a behavioral curiosity component and compared the ability of this new measure with the capability of the most commonly used self-control scale in predicting a crime/deviance index. Data was derived from a convenience sample of college students. As theoretically predicted, self-control was significantly correlated with curiosity, and the curiosity scale significantly predicted the crime/deviance index, beyond the effects of the self-control scale. More conservative tests demonstrated that curiosity also significantly predicted involvement in more specific illegal/deviance measures, including those involving somewhat serious delinquent/criminal conduct. The findings led us to conclude that curiosity may be another additional cause of crime/deviance beyond the effects of self-control, curiosity explains more than just involvement in exploratory types of illegal/deviant behavior, and that curiosity has been an overlooked concept in the crime/deviance decision-making process.